Ibu sebagai Pemberi Asuh Anak dengan Hidrosefalus: Pergumulan dalam Kemiskinan dan Kasih Sayang - Bio Adha Adiputra; Aloysius Soesilo (Airlangga University Press, Universitas Airlangga, 2022)
Hydrocephalus is a heterogeneous and complex condition in terms of its pathogenesis, symptoms andpsychological implications for the sufferers and their families. Having a child with hydrocephalus in themidst of low economic conditions is a complex journey for a caregiver. This qualitative research with aphenomenological approach focused on the subjective or psychological experience of mothers as theprimary caregiver for children with hydrocephalus. From a social foundation engaged in support forhydrocephalus, two participants were recruited with low socioeconomic status and were able toarticulate their subjective experiences from the moment they discovered their child had hydrocephalusto their daily involvement in providing care within economic constraints. Results showed that in orderto survive and accept reality, the two participants and their respective husband must experience notonly personal, but also communal or social emotional struggles So far, they had been able to maintaincare for their child with hydrocephalus owing to social support from fellow parents and family.